Enhancing Libyan EFL Undergraduate Students’ Awareness of Mobile Applications for Learning English in the English Department at Sirte University - Sumaia Omran Alzarga; Mabroka Masoud Bleed; Telees Abd Alnabi Rajab (Abhat Journal, 2023)
To master any language, the most important and effective method is to practice it endlessly. The purpose of this research is to investigate whether students are aware of using mobile applications (apps) for learning English. Furthermore, this study aims to evaluate the extent to which students are using mobile applications for learning English. The participants of this study were 20 students from the English department at Sirte University. A semi-structured questionnaire adopted from Mospan (2015) was used to collect the data. This research used both quantitative and qualitative research designs; the quantitative data was analyzed manually, and content analysis was applied to the qualitative data. The results of the study revealed that a vast majority of participants reported that they are motivated to use mobile applications for learning English. Participants were also aware of autonomous learning (self-study). However, there were some hinderances preventing students from using mobile apps for learning English.